Drinking Water Salinity, Urinary Macro‐Mineral Excretions, and Blood Pressure in the Southwest Coastal Population of Bangladesh. Issue 9 (7th May 2019) - Naser, Abu Mohd; Rahman, Mahbubur; Unicomb, Leanne; Doza, Solaiman; Gazi, Mohammed Shahid; Alam, Gazi Raisul; Karim, Mohammed Rabiul; Uddin, Mohammad Nasir; Khan, Golam Kibria; Ahmed, Kazi Matin; Shamsudduha, Mohammad; Anand, Shuchi; et al.
Abstract : Background: Sodium (Na + ) in saline water may increase blood pressure (BP), but potassium (K + ), calcium (Ca 2+ ), and magnesium (Mg 2+ ) may lower BP. We assessed the association between drinking water salinity and population BP. Methods and Results: We pooled 6487 BP measurements from 2 cohorts in coastal Bangladesh. We used multilevel linear models to estimate BP differences across water salinity categories: fresh water (electrical conductivity, <0.7 mS/cm), mild salinity (electrical conductivity ≥0.7 and <2 mS/cm), and moderate salinity (electrical conductivity ≥2 and <10 mS/cm). We assessed whether salinity categories were associated with hypertension using multilevel multinomial logistic models. Models included participant‐, household‐, and community‐level random intercepts. Models were adjusted for age, sex, body mass index (BMI), physical activity, smoking, household wealth, alcohol consumption, sleep hours, religion, and salt consumption. We evaluated the 24‐hour urinary minerals across salinity categories, and the associations between urinary minerals and BP using multilevel linear models. Compared with fresh water drinkers, mild‐salinity water drinkers had lower mean systolic BP (−1.55 [95% CI: −3.22–0.12] mm Hg) and lower mean diastolic BP (−1.26 [95% CI: −2.21–−0.32] mm Hg) adjusted models. The adjusted odds ratio among mild‐salinity water drinkers for stage 1 hypertension was 0.60 (95% CI: 0.43–0.84) and for stage 2 hypertension was 0.56 (95% CI: 0.46–0.89). Mild‐salinity water drinkers had high urinary Ca 2+, and Mg 2+, and both urinary Ca 2+ and Mg 2+ were associated with lower BP. Conclusions: Drinking mild‐salinity water was associated with lower BP, which can be explained by higher intake of Ca 2+ and Mg 2+ through saline water. Abstract : See Editorial Bispham and Nowak